Boosting NiO Catalytic Activity by x wt % F‐ions and K2O for the Production of Methyl Ethyl Ketone (MEK) via Catalytic Dehydrogenation of 2‐Butanol. Issue 9 (26th February 2021) - Halawy, Samih A.; Osman, Ahmed I.; Abdelkader, Adel; Yang, Haiping
Abstract: Herein, the synthesis of pure and modified mesoporous nanocrystalline NiO is reported. The catalyst was modified with different wt % F‐ions or K2 O and used to produce Methyl ethyl ketone (MEK) as a potential fuel/solvent. XRD analysis of the promoted catalysts confirmed the formation of Ni‐metal covered by the host oxide, compared with pure NiO, especially for the promoted catalysts with x wt % F‐ions. CO2 ‐TPD results demonstrated the existence of different basic sites over these catalysts with varying strength. The catalytic conversion of sec‐butanol (SB) into MEK over the parent NiO catalyst showed 52 % and 76.8 % conversion of SB at 250 and 275 °C, respectively, with higher selectivity to MEK >96 %. Among the promoted catalysts, NiO‐10 wt % F − and NiO‐1 wt % K2 O catalysts showed 99 and 95 % conversion, respectively, with retaining the MEK selectivity of ≥96 %. The catalytic activity, of the most active catalysts, was correlated with the presence of Ni/NiO interfaces, different types of basic sites, especially strong basic sites, and the surface area and porosity measurements. Abstract : Just got promoted ! A highly active and selective promoted Ni‐based catalyst is effective for the production of Methyl Ethyl Ketone via the catalytic dehydrogenation of secondary butanol at low reaction temperatures. The catalyst promoters were added to the Ni‐based catalyst using simple and facile promotion using F‐ions or K2 O. The catalytic activity, of the most active catalysts, was correlated with the presence of Ni/NiO interfaces, different types of basic sites, especially strong basic sites, and the surface area and porosity.